Foam and method for producing the same
Patent Information
- Application Number
- JP2024108975
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2039-07-08
AI Technical Summary
Existing foams lack thermal sensitivity, cushioning properties, flexibility, and mechanical properties, making them difficult to mold into irregular shapes and compromising ease of handling and durability.
A foam composition comprising a thermoplastic resin with finely dispersed zirconium oxide, which is present as a dispersed phase with an average diameter of 10 μm or less, allowing for thermal sensitivity and cushioning properties without compromising mechanical properties.
The foam exhibits both thermal sensitivity and cushioning properties, is easily moldable into various shapes, and maintains excellent flexibility and mechanical properties.
Abstract
Description
[Technical field]
[0001] The present invention relates to a foam having warmth-sensing and shock-absorbing properties and a method for producing the same. [Background technology]
[0002] Daily necessities (kotatsu mats, kitchen mats, etc.), outdoor equipment, disaster prevention goods, pets In the fields of bedding and bedding products, As a warming product with a cushioning effect, a foam sheet with aluminum foil attached is widely used. The foam sheet is used to reflect near-infrared and far-infrared rays, which are heat sources. and a method for expressing a warm sensation.
[0003] Japanese Patent Application Laid-Open No. 2019-38198 (Patent Document 1) describes a phenolic resin foam layer and A surface layer is provided on at least one surface of the foam layer via a flexible surface material, However, a foamed resin laminate is disclosed in which the metal layer is covered with a protective layer. It is described that the phenolic resin foam layer is used as a heat insulating material in various fields. In the examples, it is described that the device is installed on a sloped roof, improving workability.
[0004] In JP 2017-141342 A (Patent Document 2), a thermoplastic resin and an elastomer and a foam comprising a skin region and a core region. Examples of fillers, which are optional components that may be contained in the foamed molded article, include many inorganic compounds. However, the particle size is not disclosed, and it is not included in the examples.
[0005] Japanese Patent Application Laid-Open No. 2019-38997 (Patent Document 3) describes a resin used for heat dissipation in electronic devices. As the adhesive sheet, a foamed resin sheet with an adhesive layer is disclosed. As the first thermal conductive particles having an average particle size of 0.1 μm or more and less than 5 μm, A thermally conductive adhesive is described that includes a second thermally conductive particle of 30 μm, and the adhesive layer is a foam. In the embodiment, the adhesive layer is made of hydroxypropyl acrylate having an average particle size of 1 μm. A non-foaming viscous liquid containing aluminum hydroxide powder and aluminum hydroxide powder with an average particle size of 8 μm was used. An adhesive layer is prepared.
[0006] On the other hand, in order to give the foamed resin itself a warm sensation, metal oxides that emit far infrared rays are used. Foam sheets containing additives such as cellulose acetate and cellulose acetate-containing polyethersulfone have also been proposed.
[0007] In Utility Model Registration No. 3113678 (Patent Document 4), a polyethylene resin is Aluminum, titanium oxide, or zirconium oxide, either alone or in combination, A sheet for improving blood flow, the sheet having a structure in which the surface of the sheet-shaped crosslinked foam is at least has been disclosed.
[0008] In Japanese Patent Laid-Open Publication No. 2003-327733 (Patent Document 5), the inorganic natural mineral colomanite is a first step of calcining the calcined colomanite to form a calcined colomanite; Mix 10 to 20 parts of metal oxide with 100 parts of polyethylene resin. A second step of adding at least a foaming agent, kneading and foaming to obtain a polyethylene foam. The polyethylene foam obtained in the second step is sliced to a desired thickness. and a third step of forming a sheet by using the above-mentioned method. It is being done.
[0009] In Japanese Patent Publication No. 2004-518793 (Patent Document 6), a particle having a particle diameter of less than about 100 nm is included in the vehicle. A foam composition is disclosed that contains 100% surface-modified nanoparticles. The nanoparticles used are nanosilica modified with a silane coupling agent. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2019-38198 A [Patent Document 2] JP 2017-141342 A [Patent Document 3] JP 2019-38997 A [Patent Document 4] Utility Model Registration No. 3113678 [Patent Document 5] JP 2003-327733 A [Patent Document 6] Special Publication No. 2004-518793 Summary of the Invention [Problem to be solved by the invention]
[0011] However, none of Patent Documents 1 to 3 describes the use of foam as a warming product. It hasn't been done yet.
[0012] In addition, when the foam of Patent Document 1 is used as a warming product, a metal foil is attached to the foam. Since it is made of a material that is mixed together, it is difficult to handle and is therefore flexible. It is difficult to do so.
[0013] On the other hand, in Patent Documents 2 and 3, inorganic particles are blended into the foam as a filler or thermal conductive agent. However, no foam containing the inorganic particles has been prepared.
[0014] In Patent Documents 4 and 5, the foam contains a large amount of metal oxide, which reduces the mechanical properties of the foam. Moreover, the particle size of the metal oxide is unknown. Since the foam is made of a thin film, it is difficult to mix the foaming raw materials, and it is difficult to obtain a foam in which the metal oxide is uniformly dispersed. You can't even get a body.
[0015] In addition, in Patent Documents 6 and 7, the expansion ratio is unknown and there is no description of the warmth sensation. Furthermore, the applications of Patent Document 7 are mostly low foaming materials.
[0016] Therefore, an object of the present invention is to provide a foam and a cushioning material that can provide both warmth and cushioning properties. The present invention also aims to provide a method for producing the same.
[0017] Another object of the present invention is to provide a foam that can be easily molded into various three-dimensional shapes and a method for producing the same. The purpose of this invention is to provide
[0018] A further object of the present invention is to provide a foam having excellent flexibility and excellent touch, and a method for producing the same. The purpose of the Act is to provide a law.
[0019] Another object of the present invention is to provide a foam having excellent mechanical properties and heat retention properties, and a method for producing the same. The purpose of the Act is to provide a law. [Means for solving the problem]
[0020] As a result of intensive research into achieving the above object, the present inventors have found that a small amount of silica gel is contained in the foam. By finely dispersing konium, it is possible to express a warm sensation even with a simple and homogeneous structure. They also found that the shock-absorbing properties (cushioning properties) were not impaired, and thus completed the present invention.
[0021] That is, the foam of the present invention is a resin composition comprising a thermoplastic resin and / or a crosslinked product thereof. and zirconium oxide, wherein the proportion of said zirconium oxide is greater than the proportion of said resin. 0.01 to 8 parts by mass per 100 parts by mass of the oil component, The zirconium oxide is dispersed as a dispersed phase in the mixture, and the average diameter of the dispersed phase is 10 μm or less. The foam may have an expansion ratio of 10 times or more. The resin component may be a polyethylene-based resin. The foam may further contain silicon oxide (particularly, silica gel). The zinc may be localized near the walls and / or skin of the voids. The foam may be a warm foam capable of releasing heat.
[0022] The present invention relates to a method for foaming a foamable resin composition comprising a raw resin component and zirconium oxide. The foamable resin composition also includes a foaming agent as a matrix. The raw material resin component may have a dispersed phase in which zirconium oxide is dispersed. The foamable resin composition may have an average diameter of 100 nm or less. In the first raw material resin component, zirconium oxide is dispersed as a dispersed phase in molecular or atomic units. The master batch may be combined with the second raw material resin component. Effect of the Invention
[0023] In the present invention, a small amount of zirconium oxide is finely dispersed in the foam, so that the zirconium oxide is not separated from the foam. There is no need to form a layer to express the warmth sensation, and the structure is simple and homogeneous (simple single layer structure). Even if the material is made of a material with a different structure, it is possible to achieve both warmth and cushioning properties. It can be easily molded into any shape, has excellent flexibility, and is soft to the touch. The zirconium oxide is finely dispersed, so it has excellent mechanical properties. The warm sensation is not expressed by reflection, but by absorbing far infrared rays with zirconium oxide. It also has heat-retaining properties because it absorbs and releases heat. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] [Resin component] The foam of the present invention contains a thermoplastic resin or a crosslinked product thereof as a resin component.
[0025] Examples of the thermoplastic resin include olefin resin, styrene resin, and vinyl chloride resin. Grease, vinyl acetate resin, polyvinyl alcohol resin, acrylic resin, polyacetal resins, polyester resins, polycarbonate resins, polyamide resins, and these resins These thermoplastic resins include thermoplastic elastomers containing the following components: Of these thermoplastic resins, olefin-based Thermoplastic containing resins are preferred.
[0026] The olefin resin may be any polymer that contains olefin units as a main component. The resins include olefin homopolymers and copolymers.
[0027] Examples of olefins include ethylene, 1-propylene, 1-butene, isobutene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene C, such as 1-hexadecene, 1-octadecene, and 1-eicosene 2-20 α-straight chain olefins; 3-methyl-1-butene, 2-methyl-1-pentene, 3-methyl-1- Pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl C such as 3-ethyl-1-hexene and 3-ethyl-1-hexene 2-20 α-Branched Olefins ;Cyclobutene, cyclopentene, cycloheptene, cyclooctene, etc. 4-12 S Chloroolefin; 2-Norbornene, 5-Methyl-2-Norbornene, 5,5-Dimethyl -2-norbornene and other polycyclic olefins.
[0028] These olefins can be used alone or in combination of two or more. , α-C 2-8 Olefins are preferred, α-C 2-4 Olefins are more preferred, with ethyl Ethylene and / or propylene are most preferred.
[0029] The olefin resin may be a copolymer of the above-mentioned olefin and a copolymerizable monomer. Examples of the copolymerizable monomer include ethylenically unsaturated carboxylic acids and (meth)acrylic acid. Esters, vinyl esters of carboxylic acids, polymerizable nitrile compounds, aromatic vinyls, conjugated dienes Examples of such copolymers include conjugated dienes and non-conjugated dienes.
[0030] Ethylenically unsaturated carboxylic acids include ethylenically unsaturated carboxylic acids and their derivatives. Water can be used, for example, (meth)acrylic acid, (anhydrous) maleic acid, fumaric acid, itaco Examples include cyclic acid, citraconic acid, crotonic acid, isocrotonic acid, mesaconic acid, and angelic acid. Can be obtained.
[0031] Examples of (meth)acrylic acid esters include methyl acrylate and ethyl acrylate. , (meth)acrylic acid C such as methyl methacrylate 1-6 Alkyl esters, glycidyl (Meth)acrylates and the like.
[0032] Examples of vinyl carboxylates include vinyl acetate and vinyl propionate. Saturated carboxylic acid vinyl esters and the like.
[0033] Examples of the polymerizable nitrile compound include (meth)acrylonitrile. .
[0034] Examples of aromatic vinyls include styrene, vinyl toluene, and α-methyl styrene. Some examples include:
[0035] Conjugated dienes include, for example, butadiene, isoprene, pentadiene, 2,3-di Methylbutadiene, etc.
[0036] Examples of non-conjugated dienes include 1,4-hexadiene, 1,6-octadiene, 2 -Methyl-1,5-hexadiene, 4-methyl-1,4-hexadiene, 5-methyl-1 ,4-Hexadiene, Dicyclopentadiene, 5-Vinylnorbornene, 5-Ethylidene -2-norbornene, etc.
[0037] These copolymerizable monomers may be used alone or in combination. The proportion of the monomer is 0 to 50 mol %, preferably 0.1 to 30 mol %, more preferably The content is preferably 1 to 10 mol %.
[0038] The copolymers (copolymers of olefins and copolymers of olefins and copolymerizable monomers) Copolymers) include random copolymers, alternating copolymers, block copolymers, and graft copolymers. The copolymers include, but are typically random or alternating copolymers.
[0039] These olefin resins can be used alone or in combination. Among the olefin resins, polyethylene resins and polypropylene resins are the most popular from the viewpoint of foaming properties. Poly C resins 2-3 Olefin-based resins (particularly polyethylene-based resins) are preferred.
[0040] Examples of polyethylene resins include low-density polyethylene (LDPE), linear low-density polyethylene (LDPE), Low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE) and other ethylene homopolymers; ethylene-propylene copolymers, ethylene- Butene-1 copolymer, ethylene-propylene-butene-1 copolymer, ethylene-(4-methyl- Tetrylene-1) copolymer, ethylene-vinyl acetate copolymer (EVA resin), ethylene -methyl methacrylate copolymers and other copolymers whose main component is ethylene. These polyethylene resins can be used alone or in combination. Among these polyethylene resins, LDPE, LLDPE, and EVA are the most popular from the viewpoint of foaming property. Resins and the like are preferred.
[0041] The number average molecular weight of the polyethylene resin is, for example, 10,000 to 300,000, preferably 15,000 to 20,000. The molecular weight is preferably 0,000, and more preferably 20,000 to 100,000. In the gel chromatography (GPC) method, the measurement temperature was 140°C and the solvent was ortho-dichlorobenzene. Using chlorobenzene and a column (Shodex GPC AD-806MS), It can be measured using universal calibration with Listyl acetate as the standard.
[0042] The melt flow rate (MFR) of polyethylene resin is based on JIS K7210. The method (190°C, load 21.2N) may be 0.1g / 10min or more, for example, 0 0.1 to 60 g / 10 min, preferably 0.2 to 25 g / 10 min, more preferably 0.25 The MFR is preferably 0.3 to 5 g / 10 min. There is a risk of the foaming property and strength decreasing, and conversely, if the value is too small, there is a risk of the foaming property decreasing. It is generally known that as the MFR increases, the melt tension decreases and the bubbles tend to break. However, by adjusting the lower limit of the MFR to the above range, the foaming property can be improved.
[0043] The melting point of the polyethylene resin (DSC method) is, for example, 80 to 150°C, preferably 90 to The temperature is preferably 140°C, more preferably 100 to 130°C. The melting point is, for example, 70 to 140° C., preferably 80 to 130° C., and more preferably 90 to 1 It is 20 degrees Celsius.
[0044] Examples of polypropylene-based resins include polypropylene, which is a homopolymer of propylene. Propylene; propylene-ethylene copolymer, propylene-(meth)acrylic acid copolymer, propylene Examples include copolymers mainly composed of propylene, such as propylene-ethylene-butene-1. These polypropylene resins can be used alone or in combination. Among these polypropylene-based resins, polypropylene, propylene-ethylene copolymers, etc. etc. are preferred.
[0045] The number average molecular weight of the polypropylene resin is, for example, 10,000 to 500,000, preferably 15,000 to The number average molecular weight of the polypropylene resin is preferably 300,000, and more preferably 20,000 to 100,000. The molecular weight can be measured by gel permeation chromatography (GPC). The number average molecular weight of the polypropylene resin is determined by measuring the number average molecular weight of the polyethylene resin. It can be measured under the same conditions as the standard method.
[0046] The melting point of the polypropylene resin (DSC method) is, for example, 120 to 180° C., preferably 1 The temperature is preferably 30 to 175°C, and more preferably 140 to 170°C. The cut softening point is, for example, 110 to 170°C, preferably 120 to 165°C, and more preferably The temperature is usually 130 to 160 degrees Celsius.
[0047] The MFR of polypropylene resin is measured according to JIS K7210 (230℃, load 21.2N), it may be 0.1g / 10min or more, for example, 0.1 to 50g / 10min. , preferably 0.2 to 30 g / 10 min, more preferably 0.25 to 10 g / 10 min, and most preferably The MFR is preferably 0.3 to 5 g / 10 min. If the MFR is too small or too large, There is a risk that the foaming properties and strength may decrease.
[0048] When the thermoplastic resin contains an olefin-based resin, the thermoplastic resin is an olefin-based resin alone. The olefin resin and the thermoplastic resin other than the olefin resin (other thermoplastic resin) may be used. The olefin resin may be combined with another thermoplastic resin. As the resin, a styrene-based resin is preferable because it can improve the rigidity of the foam. Thermoplastic elastomers (e.g., olefin-based thermoplastic elastomers) are preferred because they can improve flexibility. Thermoplastic elastomers, styrene-based thermoplastic elastomers, etc. are preferred.
[0049] The mass ratio of olefin resin to other thermoplastic resin is olefin resin / other thermoplastic resin. Resin = Select from a range of 100 / 0 to 10 / 90 (e.g. 100 / 0 to 50 / 50) When combined with other thermoplastic resins, the ratio of olefin resin to other thermoplastic resins is 9. 9 / 1 to 30 / 70, preferably 98 / 2 to 50 / 50, more preferably 95 / 5 to 7 The ratio of the olefin resin is preferably 0 / 30, and more preferably 93 / 7 to 80 / 20. The content of the thermoplastic resin is preferably 50% by mass or more, more preferably 80% by mass or more (particularly 90% by mass or more). % by mass or more), and may be 100% by mass (olefin-based resin only). If the proportion of the base resin is too low, there is a risk of the foaming property decreasing.
[0050] The resin component may be a crosslinked thermoplastic resin for applications requiring durability. The crosslinked body may be a conventional crosslinked body depending on the type of thermoplastic resin. In the case of an olefin resin, the crosslinked product is a conventional olefin resin crosslinked product, for example, a water crosslinked product. The crosslinked product may be a chemically crosslinked product, a radiation crosslinked product, or an electron beam crosslinked product. From the standpoint of productivity, etc., a water-crosslinked product is preferred.
[0051] The water-crosslinked material is an olefin having a water-crosslinkable hydrolytic condensable silyl group (water-crosslinkable silyl group). It is sufficient that the olefin resin is a water-crosslinked product, and the monomer constituting the main chain is a hydrolysis-condensation-type monomer. The polymer may be a crosslinked product of a polymer obtained by using a monomer having a silyl group of the formula: It is a polymer in which a monomer having a hydrolytic condensation silyl group is graft-polymerized onto the main chain of the resin. As such a water-crosslinked olefin resin, for example, The water-crosslinked bodies described in JP-A-2016-37551 and JP-A-2016-37552 can be used. do.
[0052] [Zirconium oxide] The foam of the present invention is made of zirconium oxide (zirconia or Zirconium dioxide is a material that absorbs and emits far infrared rays. In the present invention, the resin component contains By including zirconium oxide as a dispersed phase, the cushioning properties and flexibility of the foam are impaired. In particular, zirconium oxide is contained in the resin component as a matrix. By finely dispersing the rubber as a dispersed phase, even a small amount of rubber can impart high thermal sensitivity to the foam. It is possible to impart high foaming properties and mechanical properties to the composition.
[0053] The average diameter of the dispersed phase (zirconium oxide) finely dispersed in the matrix is 10 μm or less (e.g. For example, about 0.01 to 10 μm, for example, 0.1 to 5 μm, preferably 0.3 The particle size is preferably 0.01 to 3 μm, more preferably 0.5 to 2 μm, and most preferably 1 to 1.5 μm. The average diameter of the dispersed phase may be nanometer-sized, for example, 100 nm or less. Preferably, the thickness is 50 nm or less, and more preferably, the thickness is 30 nm or less (for example, 0.1 to 10 nm). In addition, when the dispersed phase has an anisotropic shape, the diameter of each dispersed phase may be determined by the ratio of the major axis to the minor axis. The average value of the diameter is indicated.
[0054] Furthermore, the dispersed phase (zirconium oxide) finely dispersed in the matrix improves the warmth sensation. It is preferable that the pores are localized near the wall surfaces and / or skin layer of the voids in order to avoid the pores being too rough.
[0055] In the present specification and claims, the average diameter and dispersion state of the dispersed phase are determined by scanning electron microscopy. Observation with a scanning electron microscope (SEM) and elemental analysis with an energy dispersive X-ray spectrometer (EDS elemental analysis) In detail, it can be measured by the method described in the Examples below.
[0056] Zirconium oxide is a material that has not been surface-treated due to its warmth and dispersibility. Ninium is preferred.
[0057] In the present invention, the proportion of zirconium oxide is relatively small, so that the foaming property and functionality of the foam are improved. The mechanical properties can be improved. Specifically, the ratio of zirconium oxide in the foam is 10 mass% or less. (For example, about 0.001 to 10% by mass) is acceptable, but functionality can be expressed even in small amounts. Therefore, from the viewpoint of improving the inherent properties of the foam, the content is 5 mass % or less (for example, 0.01 to 5 % by mass, for example, 0.03 to 5% by mass (for example, 0.05 to 4% by mass), Preferably, it is 0.1 to 3 mass% (for example, 0.2 to 2 mass%), and more preferably, it is 0.3 to 1. The ratio of zirconium oxide to the resin composition is preferably 0.5 to 1 mass %, and more preferably 0.5 to 1 mass %. The amount is 0.01 to 8 parts by mass, preferably 0.01 to 5 parts by mass, based on 100 parts by mass of the mixture. More preferably, it is 0.1 to 3 parts by mass, more preferably, it is 0.3 to 2 parts by mass, and most preferably, it is 0 If the proportion of zirconium oxide is too high, the foaming property and functionality of the foam may deteriorate. There is a risk of the mechanical properties being reduced.
[0058] [Silicon oxide] The foam of the present invention contains, in addition to the resin component and zirconium oxide, a zirconium oxide fraction. It also contains silicon oxide (silica or silicon dioxide) to improve dispersibility. Good too.
[0059] Examples of silicon oxide (silica) include dry silica (dry process) such as fumed silica. White carbon; wet silica such as colloidal silica, silica gel, and precipitated silica (wet These silicon oxides may be used alone or in combination. The silicon oxide may be surface-treated silica. Of these silicas, silica gel is preferred, and type B silica gel is particularly preferred.
[0060] The particle size of silicon oxide is, for example, 1000 μm or less as mesh passing particles by sieving. Preferably, the thickness is 500 μm or less, more preferably 100 μm or less, and most preferably 50 If the silica particle size is too large, the mechanical properties of the foam may be reduced. .
[0061] Silicon oxide may be either non-porous or porous, but is preferably nitrogen-deposited by the BET method. The adsorption specific surface area is, for example, 100 to 1000 m 2 / g, preferably 200 to 800m 2 / g , and more preferably 300 to 700 m 2 / g, most preferably 400 to 600m 2 / g If the specific surface area is too large, it may be difficult to disperse the particles uniformly. If the thickness is too small, the mechanical properties of the foam may be reduced.
[0062] The ratio of silicon oxide is 10 parts by mass or more per 100 parts by mass of zirconium oxide. For example, the amount is 10 to 5,000 parts by mass, preferably 50 to 3,000 parts by mass, and more preferably Preferably, the amount is 100 to 1000 parts by mass, more preferably 200 to 500 parts by mass, and most preferably 2 If the proportion of silicon oxide is too low, the dispersion of zirconium oxide becomes poor. There is a risk that the effect of improving the performance may be reduced.
[0063] [Foaming agent] The foam of the present invention is produced by foaming a foamable resin composition containing the resin component and zirconium oxide. The foamable resin composition obtained by foaming may contain a foaming agent.
[0064] As the foaming agent, a conventional foaming agent can be used, and it may be a decomposable foaming agent (chemical foaming agent). However, volatile foaming agents (physical foaming agents) are preferred because they can improve the foaming ratio in a simple manner. Examples of volatile blowing agents include inorganic blowing agents (nitrogen, carbon dioxide, oxygen, air, etc.). Water, etc.), organic blowing agents (aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, chlorinated carbon Hydrogen fluoride, hydrocarbon fluoride, alcohols, ethers, aldehydes, ketones, etc. Among these, butane (n-butane, isobutane) is the most popular because it is inexpensive and has low toxicity. Lower aliphatic hydrocarbons such as ethane (n-pentane, isopentane, etc.) and pentane (n-pentane, isopentane, etc.) It is widely used.
[0065] The ratio of the foaming agent is, for example, 0.01 to 30 parts by mass relative to 100 parts by mass of the resin component, preferably or 0.1 to 25 parts by mass, more preferably 1 to 20 parts by mass, and most preferably 5 to 15 Parts by mass.
[0066] [Foam nucleating agent] The foam of the present invention may further contain a foam nucleating agent. Examples of the foam nucleating agent include Silicon compounds (talc, silica, zeolite, etc.), inorganic acid salts (sodium bicarbonate, carbonate Carbonates such as calcium, magnesium carbonate, sodium bicarbonate, and ammonium carbonate or bicarbonate, etc.), organic acids or their salts (citric acid, sodium citrate, stearyl calcium stearate, aluminum stearate, zinc stearate, etc.), metal oxides (acids zinc oxide, titanium oxide, aluminum oxide, etc.), metal hydroxides (aluminum hydroxide, etc. These foaming nucleating agents can be used alone or in combination of two or more. do.
[0067] The ratio of the foaming nucleating agent is, for example, 0.01 to 10 parts by mass, preferably 0.01 to 10 parts by mass, based on 100 parts by mass of the resin component. Preferably, it is 0.05 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, and most preferably 0. 5 to 2 parts by mass.
[0068] [Shrinkage prevention agent] The foam of the present invention may further contain a shrinkage inhibitor. Examples of the shrinkage inhibitor include For example, fatty acid esters (mono- or triglyceride palmitate, mono- or triglyceride stearic acid C such as triglycerides 8-24 Esters of fatty acids and polyhydric alcohols, etc. Amido (palmitic acid amide, stearic acid amide, etc.) 8-24 fatty acid amides, etc. These shrinkage inhibitors can be used alone or in combination. .
[0069] The proportion of the shrinkage inhibitor is, for example, 0.01 to 30 parts by mass relative to 100 parts by mass of the resin component. Preferably, it is 0.05 to 20 parts by mass, more preferably, it is 0.1 to 10 parts by mass, and most preferably is 1 to 5 parts by mass.
[0070] [Other additives] The foam of the present invention may further contain other additives such as conventional additives. Additives include colorants (dyes, pigments, etc.), surface smoothing agents, foam regulators, stabilizers (oxidants, etc.), inhibitors, heat stabilizers, UV absorbers, etc.), viscosity regulators, compatibilizers, dispersants, antistatic agents , anti-blocking agents, anti-fogging agents, fillers (calcium carbonate, carbon fiber, etc.), lubricants, release agents agents, lubricants, impact modifiers, plasticizers, flame retardants, biocides (bactericides, bacteriostatic agents, antifungal agents, These conventional additives include preservatives, insect repellents, antiallergic agents, and deodorants. can be used alone or in combination of two or more.
[0071] The total proportion of other additives is, for example, 0.01 to 30 parts by mass per 100 parts by mass of the resin component. parts by mass, preferably 0.05 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, and most preferably The content is preferably 1 to 5 parts by mass.
[0072] [Foam characteristics] The foam of the present invention has not been actively added in the past because of the deterioration of foaming properties. Although it contains inorganic compounds, it can improve the foaming property. 10-fold or more (particularly 10-fold or more), for example, 3 to 100-fold, preferably 5 to 80-fold, More preferably, it is 10 to 50 times, more preferably, it is 15 to 40 times, and most preferably, it is 20 to 30 times. If the expansion ratio is too low, the cushioning properties and flexibility may decrease.
[0073] The foam of the present invention has a closed cell and / or open cell structure, and at least It is preferable that the porous structure contains a vertical cell structure, and the ratio of open cells to the total number of cells (the sum of open cells and closed cells) is 1.0 to 1.0. The open cell ratio, which is the ratio of the bubbles, may be 90% by volume or less, for example, 0.1 to 90% by volume. %, preferably 1 to 80% by volume, more preferably 3 to 50% by volume, and most preferably 5 to If the open cell ratio is too high, the mechanical properties of the foam may be reduced. In the present invention, since zirconium oxide is finely dispersed in the thermoplastic resin, it is difficult to form independent bubbles. Despite the use of zirconium oxide, a common inorganic compound, such high independent porosity was achieved. On the other hand, for applications requiring flexibility, a foam with a high open cell ratio is preferred. For example, the open cell ratio may be more than 90 volume %. For example, the composition of the resin components other than the master batch may be changed. .
[0074] The average cell diameter of the foam of the present invention is, for example, 0.2 to 2 mm, preferably 0.3 to 1.8 mm. m, more preferably 0.4 to 1.6 mm, and most preferably 0.5 to 1.3 mm. If the average bubble diameter is too small, it may be difficult to increase the expansion ratio. However, there is a risk of the mechanical properties being deteriorated.
[0075] The foam of the present invention preferably has a skin layer on the surface. The coverage may be 60% by area or more (particularly 80% by area or more), and preferably 90% by area. The skin layer may be 100% by area (the entire surface is the skin layer). It means a non-foamed layer that extends with a substantially uniform thickness on the surface of a foam.
[0076] The average thickness of the skin layer can be selected from the range of about 0.001 to 1 mm. For example, 5 to 0.1 mm, preferably 0.008 to 0.05 mm, and more preferably 0.01 to 0 The average thickness of the skin layer is preferably 0.03 mm, and more preferably 0.012 to 0.025 mm. If the thickness is too thin, the handling property may be deteriorated, whereas if the thickness is too thick, the foaming property may be deteriorated. do.
[0077] In the present specification and claims, the expansion ratio, open cell ratio, average cell diameter, and The average thickness of the skin layer can be measured by the method described in the Examples below.
[0078] The foam of the present invention may be a thermosensitive foam capable of releasing heat. The foam has excellent absorption and emission properties for far-infrared rays with wavelengths of 10 μm or more, and is particularly effective at absorbing and emitting far-infrared rays with wavelengths of 1 It has excellent absorption and emission properties for far infrared rays of about 0 to 20 μm, so it provides warmth to the human body. can be effectively granted.
[0079] [Method of manufacturing foam] The method for producing a foam of the present invention comprises the steps of: Any method for foaming a foamable resin composition containing ruthenium may be used. Generally, the resin composition can be melt-kneaded and foam-molded. As the resin composition, a foamable resin composition in which zirconium oxide is finely dispersed in the raw resin component is used. It is preferable to use
[0080] The average diameter of the zirconium oxide finely dispersed in the foamable resin composition is less than 100 nm. It is acceptable for the thickness to be 50 nm or less, preferably 30 nm or less (e.g., 0.1 The dispersed phase may be dispersed in the matrix on a molecular or atomic level. In the present invention, it is particularly preferable to use zirconium oxide as the resin composition before foaming. Since a composition in which zirconium is finely dispersed is used, the obtained foam also contains zirconium oxide. It is possible to finely disperse zirconium oxide on the wall surface of the void and / or near the skin layer. Can be localized.
[0081] As a method for preparing a foamable resin composition in which zirconium oxide is finely dispersed, The raw material resin component (especially olefin-based resin) is heated while the rubber is dissolved or dispersed in a solvent. The resin composition is mixed with the raw resin component, and the solvent is removed in a gaseous state from the resin composition in a molten state. The zirconium oxide used as the raw material is nanometer-sized. Examples of the solvent for dissolving or dispersing zirconium oxide include water and aqueous organic solvents. Solvents (e.g., lower alcohols such as ethanol and isopropanol, ketones such as acetone, etc.) Among these solvents, water is preferred. The concentration of the aqueous dispersion is For example, the content is about 10 to 50 mass %, and preferably about 20 to 40 mass %. If it does, silicon oxide is added to the drive rail together with the zirconium oxide dispersion or separately. Specifically, the foamable resin composition in which zirconium oxide is finely dispersed may be It can be prepared by the method described in JP 2016-216573 A, for example, zirconium oxide. The solution obtained by dispersing the above in the solvent and the raw material resin component are extruded in an extruder (e.g., a single screw or vented extruder). After being fed into a multi-plate twin-screw extruder, the molten raw resin components and the solution are then fed into a multi-plate twin-screw extruder. The molten raw material is fed to a kneading and dispersion section having a rotating kneading plate. The fat component and the solution are uniformly mixed by a rotating kneading plate, and then the mixture is passed through a pressure reduction line. By removing the solvent in a gaseous state from the raw material resin component, zirconium oxide is formed in the raw material resin component. Thus, a foamable resin composition is prepared in which the particles are finely dispersed with an average dispersion diameter of less than 100 nm.
[0082] The obtained foamable resin composition may be subjected to foam molding as it is, or may be used as a master batch. When the foamable resin composition is used as a master batch, In addition, the resin composition from which the solvent has been removed may be further cooled and prepared into pellets or the like. good.
[0083] When provided as a masterbatch, the first raw resin component (particularly the first olefin-based Resin) with finely dispersed zirconium oxide with an average dispersion diameter of less than 100 nm. The remaining raw material resin component, the second raw material resin component (particularly the second olefin-based resin), is The mixture may be melt-kneaded using a conventional melt-kneader, such as a single-screw or vented twin-screw extruder. In addition, in the melt-kneading of the master batch and the second raw resin component, other components (developing agent) Foaming agents and, if necessary, foam nucleating agents, additives, etc. may be blended. Zirconium oxide The finely dispersed foamable resin composition can be melt-kneaded using a conventional melt kneader, for example, a single-shaft or ventilated mixer. The mixture may be melt-kneaded using a twin-screw extruder or the like. Methods such as mixers (tumblers, V-type blenders, Henschel mixers, Nauta mixers) The masterbatch is then mixed with a mixer (such as a ribbon mixer, a mechanochemical device, or an extrusion mixer) to form a The mixture is made of a second raw resin component, and other components (foaming agent and, if necessary, foam nucleating agent, additives, etc.). etc.) may be premixed.
[0084] The foam molding method may be a conventional method, such as an extrusion molding method (e.g., a T-die method, an inflation method, etc.). Among these, the foaming method with high foaming property is The extrusion molding method is preferred since it allows the foam to be produced with high productivity.
[0085] In the extrusion molding method, the extruder may be, for example, a single screw extruder (e.g., a vented extruder etc.), twin screw extruders (for example, same-rotation twin screw extruders, counter-rotation twin screw extruders, etc.), etc. can be used. It is easy to adjust the foaming conditions and achieve a high foaming ratio, so multi-stage extrusion machines such as tandem extruders are popular. A dispenser is preferred.
[0086] In the extrusion molding method, the method of introducing the foaming agent is not particularly limited. Although the foaming agent may be added to the foamable resin composition in advance, it is possible to improve the foaming ratio by a simple method. From this viewpoint, it is preferable to introduce a volatile foaming agent (physical foaming agent) in the extruder.
[0087] The shape of the die outlet (die lip) is not particularly limited and can be selected according to the desired form. For example, one-dimensional shapes such as rods and strings, sheets, films, and two-dimensional meshes (nets) ) and other two-dimensional shapes, block, plate, column, slit, L-shape, U-shape, pie It may also be a three-dimensional shape such as a pool or ring.
[0088] The extrusion foam may be cooled by a conventional method, for example, by a cooling method using a cooler. In the cooling method using a cooler, the cooling medium is compressed air, water (cooling water), etc. Examples of cooling media include air (blower) and compressed air. cooling method, blower cooling method, water spray cooling method, cooling using a cooling jacket The temperature of the cooling medium is, for example, 0 to 60°C, preferably 5 to 5 The temperature is preferably 5°C, and more preferably 10 to 50°C.
[0089] In the method of injecting compressed air, the pressure of the air is, for example, 0.1 to 10 MPa, preferably The pressure is preferably 0.2 to 5 MPa, and more preferably 0.3 to 1 MPa. The amount of spray is, for example, 100 to 1000 liters / minute, preferably 200 to 500 liters / minute. and more preferably 250 to 400 liters / minute.
[0090] In addition, when the resin component is a crosslinked thermoplastic resin, the obtained extruded foam is In the crosslinking step of the water crosslinked product, the silyl-modified polyolefin may be crosslinked by the moisture in the air. The fins may be water-crosslinked. The crosslinking process is carried out in a non-heated state (at room temperature of about 15 to 25°C). However, in order to improve productivity, crosslinking may be performed by heating. The temperature is usually 40 to 100°C, preferably 50 to 80°C, and more preferably 55 to 70°C.
[0091] If necessary, the obtained foam (particularly, a sheet-shaped foam) may be subjected to secondary processing [e.g., Thermoforming such as air forming, pressure forming, vacuum pressure forming, and match mold forming (e.g., using a mold) (thermoforming using the same method is also acceptable).
[0092] The foaming or secondary processing or molding temperature is, for example, 70 to 300° C., preferably The heating temperature may be about 80 to 280°C, and more preferably about 85 to 260°C.
[0093] The shape of the foam can be appropriately selected depending on the application, for example, a rod shape, a sheet shape, It may be a three-dimensional shape. EXAMPLES
[0094] The present invention will be described in more detail below with reference to examples. The raw materials used in the examples and comparative examples are as follows: The properties of the resulting foams were evaluated by the following methods.
[0095] [Raw materials] LDPE: Low-density polyethylene, manufactured by Japan Polyethylene Co., Ltd., "Novatec (registered trademark)" LD LF640MA”, MFR5g / 10min Isobutane (foaming agent): Commercially available Foam nucleating agent: Talc, average particle size 15μm Shrinkage prevention agent: Boehringer Ingelheim Chemicals Co., Ltd. "Activex 32 5" Zirconium oxide: "SZR-W" manufactured by Sakai Chemical Industry Co., Ltd., average particle size 3 nm Silica: Toyota Chemical Industries, Ltd. "Toyota Silica Gel B White 400 Lower", particle size 37 μm or less (sieve (particles passing through a mesh by the separation method), BET specific surface area 450m 2 / g.
[0096] [Foam unit weight] A cylindrical foam with a diameter of 74 mm and an inner diameter of 70 mm was cut to a length of 1 m and measured with an electronic specific gravity meter (Mirage The measurements were performed using a 3-inch gyroscope (MD200S, manufactured by NYK Corporation) (n=3).
[0097] [Expansion ratio] The expansion ratio was calculated based on the following formula.
[0098] Expansion ratio (times)=density of resin composition for foam / apparent density of foam.
[0099] [Open cell ratio] The mass of the foams obtained in the examples and comparative examples was measured in advance, and the foams were placed in water and then cooled to −4°C. Leave it under a reduced pressure of 0.00 mmHg (gauge pressure) for 1 minute to allow water to penetrate into the open cell structure. The pressure was returned to atmospheric pressure from the reduced pressure state, and the water adhering to the surface of the foam was removed and the mass was measured. Thereafter, the open cell ratio was calculated according to the following formula (1).
[0100] Open cell ratio (%) = {(w2-w1) / d3} / (w1 / d1-w1 / d2) x 100 (1) (In the formula, w2 is the foam mass after water absorption, w1 is the foam mass before water absorption, and d1 is the apparent density of the foam. d2 is the apparent density of the resin composition used in the foam, and d3 is the density of water at the time of measurement. vinegar).
[0101] [Bubble diameter (cell size)] The cross section of the foam was observed using a scanning electron microscope (Hitachi's "S-4800") or a digital microscope. The bubble diameter in the TD cross section and the bubble diameter in the MD cross section were measured using a 3D microscope (Scalar Corporation). The bubble diameter was measured at 10 random points, and the average value of the 20 points was taken as the bubble diameter. The diameter of each bubble was determined as the average value of the major axis and the minor axis.
[0102] [Average foam skin thickness] Electron microscope (Scalar Corporation) and filing & 2D measurement software ( Using Artray's "AR-CNVMF", the thickness of the skin layer in the TD direction was arbitrarily set to 10 The average value was taken as the average thickness of the skin layer.
[0103] [Warmth] The foam was cut into a circular sample with a diameter of 3 cm, and the sample was analyzed by a Fourier transform infrared spectrometer. (PerkinElmer's "FT-IR SpectrumOne Frontier T") was used, and the measurement temperature was 40°C. The far-infrared spectral emissivity was measured.
[0104] Comparative Example 1 Contains 100 parts by mass of LDPE, 1.75 parts by mass of foam nucleating agent, and 3.0 parts by mass of shrinkage prevention agent. The resin composition was charged into an extruder, and 8.0 parts by mass of isobutane gas was injected into the extruder midway. After that, it is cooled to the appropriate temperature for foaming, and extruded from a ring-shaped die attached to the tip to form foam. The resulting foam was cylindrical with a width of 108 mm and a thickness of 1.83 mm and had a basis weight of 15 mm. g / m, foaming ratio 24.5 times, open cell ratio 8.8%, cell size 1.07 mm, skin layer The average thickness was 0.020 mm.
[0105] Example 1 (Preparation of Zirconium Oxide-Containing Masterbatch) 3 parts by mass of zirconium oxide, 10 parts by mass of silica, zirconium oxide is 30% by mass The silica was added to 100 parts by mass of LDPE in a dry blend, and the mixture was extruded. The mixture was fed to an extruder (the extruder described in JP 2016-216573 A) at a temperature of 150 to 160°C. The mixture was melted and kneaded at 0°C. In the melt-kneading section, multiple kneading plates were rotating. Here, the polymer and the functional agent dispersed in water are mixed uniformly, and then vacuum (negative pressure) is applied to At the same time, the moisture was removed. The molten mixture from which the moisture had been removed was fed to the extrusion section and extruded. After cooling, it is taken out and pelletized in a pelletizer to obtain a masterbatch containing zirconium oxide. Got the batch.
[0106] (Foam manufacturing) 90 parts by mass of LDPE, 10 parts by mass of master batch containing zirconium oxide, 1 part by mass of foam nucleating agent. A resin composition containing 75 parts by mass of a shrinkage inhibitor and 3.0 parts by mass of a shrinkage inhibitor was charged into an extruder, and the extrusion After injecting 8.0 parts of isobutane gas halfway through the machine, it was cooled to the optimum temperature for foaming, and the tip The foam was extruded from a ring-shaped die attached to a 97 mm wide mold to obtain a foam. It is cylindrical, 2.37 mm thick, has a basis weight of 15.8 g / m, a foaming ratio of 24.5 times, and has continuous air holes. The foam ratio was 5.5%, the cell size was 1.45 mm, and the average thickness of the skin layer was 0.015 mm.
[0107] Example 2 Instead of 90 parts by weight of LDPE and 10 parts by weight of masterbatch containing zirconium oxide The following mixture is prepared by using 80 parts by mass of LDPE and 20 parts by mass of a master batch containing zirconium oxide. The foam was produced in the same manner as in Example 1. The resulting foam had a width of 98 mm and a thickness of 2 It is cylindrical with a diameter of 1.14 mm, a basis weight of 16.2 g / m, an expansion ratio of 23.0 times, and an open cell ratio of 5.0 %, cell size was 1.00 mm, and average skin layer thickness was 0.018 mm.
[0108] Example 3 Instead of 90 parts by weight of LDPE and 10 parts by weight of masterbatch containing zirconium oxide The following mixture is prepared by using 70 parts by mass of LDPE and 30 parts by mass of a master batch containing zirconium oxide. The foam was produced in the same manner as in Example 1. The foam obtained had a width of 100 mm and a thickness of It is a 2.13 mm cylindrical foam with a basis weight of 18.0 g / m, a foaming ratio of 17.7 times, and an open cell ratio of 8. 3%, cell size was 1.14 mm, and average skin layer thickness was 0.018 mm.
[0109] Example 4 (Preparation of Zirconium Oxide-Containing Masterbatch) Zirconium oxide was produced in the same manner as in Example 1, except that the amount of silica used was changed to 30 parts by mass. Thus, a rubber-containing master batch was obtained.
[0110] (Foam manufacturing) 90 parts by mass of LDPE, 10 parts by mass of master batch containing zirconium oxide, 1 part by mass of foam nucleating agent. A resin composition containing 75 parts by mass of a shrinkage inhibitor and 3.0 parts by mass of a shrinkage inhibitor was charged into an extruder, and the extrusion After injecting 7.7 parts of isobutane gas halfway through the machine, it was cooled to the optimum temperature for foaming, and the tip The foam was extruded from a ring-shaped die attached to a 93 mm wide mold to obtain a foam. It is cylindrical with a diameter of 1.49 mm and a thickness of 1.5 mm, a basis weight of 15.0 g / m, a foaming ratio of 17.7 times, and continuous air bubbles. The foam content was 3.3%, the cell size was 1.20 mm, and the average thickness of the skin layer was 0.019 mm.
[0111] Example 5 Instead of 90 parts by weight of LDPE and 10 parts by weight of masterbatch containing zirconium oxide The following mixture is prepared by using 80 parts by mass of LDPE and 20 parts by mass of a master batch containing zirconium oxide. The foam was produced in the same manner as in Example 4. The foam obtained had a width of 62 mm and a thickness of 1 It is cylindrical with a diameter of .66 mm, a basis weight of 13.6 g / m, an expansion ratio of 14.7 times, and an open cell ratio of 9.0 %, cell size was 1.24 mm, and average skin layer thickness was 0.017 mm.
[0112] Warmth Sensitivity (Far-infrared Emissivity) of the Foams Obtained in Comparative Example 1 and Examples 1, 3, and 5 The evaluation results are shown in Table 1.
[0113] [Table 1]
[0114] As is clear from the results in Table 1, the foams of the Examples have a higher far-infrared absorbing capacity than the foam of Comparative Example 1. has a high emissivity. [Industrial Applicability]
[0115] The foam of the present invention can be used in various applications requiring warmth and cushioning properties, such as daily necessities ( mats, kitchen mats, cushions, etc.), outdoor equipment (tents, outdoor mats, etc.) etc.), disaster prevention goods (capsule tents, cold weather jackets, etc.), pet supplies (baskets, baths, etc.), It can be used for bedding products (futons, mattress pads, etc.), and bedding supplies (futons, mattress pads, etc.).
Claims
1. A foam comprising a resin component consisting of a thermoplastic resin and / or a crosslinked product thereof, and zirconium oxide, wherein the thermoplastic resin comprises an olefin-based resin, the proportion of the zirconium oxide is 0.01 to 8 parts by mass per 100 parts by mass of the resin component, the zirconium oxide is dispersed in the resin component as a dispersed phase, the average diameter of the dispersed phase is 10 μm or less, and the foam has an expansion ratio of 10 times or more.
2. 2. The foam of claim 1, wherein the average diameter of the dispersed phase is less than 100 nm.
3. 3. The foam according to claim 1, wherein the resin component is a polyethylene resin.
4. The foam according to any one of claims 1 to 3, further comprising silicon oxide.
5. 5. The foam of claim 4, wherein said silicon oxide is a silica gel.
6. The foam according to any one of claims 1 to 5, wherein the zirconium oxide is localized near the walls of the voids and / or the skin layer.
7. The foam according to any one of claims 1 to 6, which is a warm-sensing foam capable of releasing heat.
8. The method for producing the foam according to any one of claims 1 to 7, comprising foaming a foamable resin composition comprising a raw material resin component and zirconium oxide.
9. 9. The method according to claim 8, wherein the foamable resin composition has a dispersed phase in which the zirconium oxide is dispersed in the raw resin component as a matrix, and the average diameter of the dispersed phase is 100 nm or less.
10. The method according to claim 9, wherein the foamable resin composition is a combination of a master batch in which zirconium oxide is dispersed at molecular or atomic level as a dispersed phase in a first raw material resin component as a matrix, and a second raw material resin component.